Role of Ultrasound and Computed Tomography in the Evaluation of Gallbladder Malignancy - Ghafoor, Nusrat; Abedin, Naffisa; Mohiuddin, AS (Anwer Khan Modern Medical College Journal, 2017)
Background & objective: Ultrasonogram (USG) and computed tomography (CT) are often used in the evaluation of gall-bladder carcinoma. Thepresent study was conducted to determine the usefulness of USG and CT scan in diagnosing gallbladder carcinoma. Materials & Methods: This cross-sectional observational study was conducted at Department of Radiology and Imaging, BIRDEM in collaboration with the Departments of Hepato-biliary Surgery, and Histopathology of the same institute over a period of 3 years fromJuly 2004 to June 2006. A total of 42 patients (ranging from 40-80 years) were initially included on the basis of signs and symptoms of gallbladder carcinoma and underwent USG and CT scan for preoperative radiological diagnosis, its extension and operability. Following operation all the resected specimens were sent for histopathological evaluation. The diagnostic accuracies of USG and CT scan were then compared against histopathological diagnoses by using Kappa statistics. Result: In the present study, the mean age of the patients was 60 (range: 40-80) years with female preponderance. About 40% of the gall-bladder were contracted and reduced in size and 32.5% large and distended on USG examination, while 45% of the gall-bladder were contracted and reduced in size and 25% distended and large on CT examination. Approximately 40% had irregularly thickened wall and 21.2% diffusely thickened wall on USG and 30% of gallbladder wall were diffusely thickened and 45% irregularly thickened on CT scan. The present study showed hepatic parenchymal invasion to be 22.5% on USG and 42.5% on CT scan. The sensitivity and specificity of USG in diagnosing GB carcinoma were 93.9 and 71.4% respectively. Similarly, the sensitivity and specificity of CT scan in detecting GB carcinoma were 97.1 and 83.3% respectively. The test of agreement (Kappa test) revealed an almost 90% agreement between the two procedures meaning that the two diagnostic modalities are almost comparable in diagnosing gall bladder carcinoma (p<0.001). Conclusion: The study findings indicate that both USG and CT scan are ideal,non-invasive, safe imaging modalities for diagnosis of gallbladder carcinoma. CT scan has an additional advantage in defining the extension of the disease and involvement of surrounding structures including lymph nodes and hepatoduodenal ligament. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 105-111